2021
DOI: 10.1111/aphw.12293
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness meditation experiences of novice practitioners in an online intervention: Trajectories, predictors, and challenges

Abstract: Background The benefits of mindfulness interventions are well‐known, but their challenges and individual differences in reactions to these challenges are much less clear. Methods The study used a mixed‐methods design to investigate the individual trajectories of daily experiences during meditation in a sample of novice volunteers participating in a 3‐week, distance‐based, guided meditation intervention (N = 175). Results Multilevel modelling revealed individual differences in the change trajectories of the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…While there was some interest, there was poor compliance with limited reported benefits. Our study shows that compliance is a significant challenge for most remotely delivered meditation programs (43,60). For motivated participants, online meditation offers a convenient and scalable opportunity for self-improvement.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…While there was some interest, there was poor compliance with limited reported benefits. Our study shows that compliance is a significant challenge for most remotely delivered meditation programs (43,60). For motivated participants, online meditation offers a convenient and scalable opportunity for self-improvement.…”
Section: Discussionmentioning
confidence: 84%
“…Yoga and meditation approaches have been shown to improve mental health and wellbeing in the past. Online delivery of meditation has shown to be effective in improving mental health outcomes (43,44); especially for anxiety symptom relief during the COVID-19 pandemic (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, this finding could be explained by the fact that the health risks associated with the COVID-19 pandemic are vastly different across age groups, given that existing meta-analyses indicate stronger effects of resilience interventions in populations at higher risk [41]. On the other hand, older adults might differ in the quality of motivation or in the development of personality resources, such as selfregulation or reflective processes, that could predict individual differences in the outcomes of positive interventions [60]. Future research needs to replicate this finding outside the context of the COVID-19 pandemic, controlling for baseline personality resources.…”
Section: Plos Onementioning
confidence: 99%
“…In other words, SAM is less effective for people with low well-being. A previous study also suggested that brief MBIs have individual differences in their therapeutic effects (Osin & Turilina, 2022). In terms of effects on well-being, the Broaden-and-Build theory of positive emotions proposes that the improvement of positive emotions to expansion of one's thought-action repertoire which, in turn, results in more personal positive psychological resources (Fredrickson, 2004).…”
Section: T a B L Ementioning
confidence: 99%